EARLY DIAGNOSTICS OF AUTOINFLAMMATORY DISORDERS ASSOCIATED WITH POST-VIRAL CHRONIC FATIGUE SYNDROME AND COGNITIVE IMPAIRMENTS IN CHRONIC MIXED HERPES VIRAL INFECTIONS - I. V. Nesterova; E. O. Khalturina (Медицинская иммунология, 2021)
The steady increase in the number of autoimmune diseases and immune-mediated autoinflammatory processes causes an increased interest of doctors of all specialties in this topic and makes the issue of early detection of autoimmune disorders / autoimmune syndrome (AS) extremely urgent. These disorders often develop against the backdrop of an atypical stream of chronic active viral infections caused by persistent viruses, in particular those of the Herpesviridae family, and remain undiagnosed due to polysymptomatic disease, and various “clinical masks” of the disorders caused by them. The semi-quantitative method developed by us for screening assessment of the content of autoantibodies in the blood serum of patients suffering from ACAI caused by herpes viruses using the ELISA method (Immunodot) is a highly specific screening method that can allow for an objective assessment of the dynamics of the autoimmune process, as well as control the effectiveness of the ongoing complex antiviral and immunomodulatory therapy. The detection of autoantibodies of various specificity in the blood serum of patients suffering from an atypical chronic active infection caused by herpes viruses (ACAI) is an early diagnostic marker, necessary, first of all, to identify autoimmune pathology of the nervous system, which is associated with a long course of the active mixed herpes-viral process.